Mineral dissolution by dimeric complexes - Xiaoxu Li; Qing Guo; Yatong Zhao; Chang Qian; Maxime Pouvreau; Trent R. Graham; Ping Chen; LiLi Liu; Chang Liu; Benjamin A. Legg; Qian Chen; Aijun Miao; et al. (Proceedings of the National Academy of Sciences, 2025)
Mineral dissolution is typically thought to occur by the detachment of monomeric building blocks of the crystal structure, although direct evidence is rare. Using in situ high-speed atomic force microscopy to examine step-edge retreat dynamics at high resolution, we report that the dissolution of gibbsite in alkaline solutions occurs mainly by the release of aluminate dimers, which subsequently dissociate into the monomeric species that dominate the solution. The observed dissolution anisotropy is readily explained by this mechanism, which was further supported by density functional tight-binding simulations of detachment activation energies. Recognition that such polynuclear dissolution mechanisms exist may enable an improved understanding of processes regulating mineral dissolution rates in nature and industry.